Responses of Corn 704 Single Cross (Zea maize) seed germination to acid rain stress - محمدشاهین دانشمندی; سیدمحسن نبوی کلات (علوم و فناوری بذر ایران, 2015)
In order to understand the response mechanism of corn (Zea maize 704 single cross) seed germination and seedling growth to acid rain stress, this study in a randomized complete design with six treatments were performed and then examined by nineteen adjective related to seed germination and seedling growth. Simulated acid rain at pH2, 3, 4, 5, 6 and control (distilled water-pH7) and then examined by nineteen adjective related to seed germination and seedling growth. The results indicated water absorption in all treatments was lower than control except pH4. the germination percentage (GP), germination energy (GE) and seedling vigour index (SI) was not changed by acid rain higher at pH2. However, was stopped all germination characteristics in pH2 (PIncreased acidity with a decline in pH2 reached zeroSeedling growth was affected by acid rain so that the control showed better results than other treatments. According to the results, water reduction acidity and toxicity of acid rain can inhibit seed germination, development and establishment of the corn